Movement disorders and their stereotactic surgical treatment: A retrospective study of 5126 patients at a single clinical center over 22 years - Yongjie Li (Elsevier, 2022)
Objectives: Based on data for a large population of patients from a single center accumulated over 22 years, the present study aimed to reveal an overall profile of movement disorders (MDs) in terms of their demographic features and surgical treatment. Methods: This study was conducted on 21,005 outpatients (2008–2019) and 5,126 inpatients (1998–2019) with MDs who underwent radiofrequency ablation (RFA) or deep-brain stimulation (DBS). Patients were categorized into those with Parkinson’s disease (PD), essential tremor (ET), dystonia, tics, or involuntary movements (IMs). The clinical data of these patients were analyzed retrospectively. Results: PD accounted for the largest proportion (75.4%) among surgically treated MD patients, and was associated with the highest surgical rate (18.8%), followed by ET (proportion: 12.1%, surgical rate: 10.4%) and dystonia (proportion: 5.7%, surgical rate: 5.7%). The male:female ratio was higher in surgical patients than in outpatients (1.49 vs. 1.27, p < 0.001). The surgery ages in patients with PD, ET, dystonia, tics, or IMs was 62 (54–67), 61 (46–68), 40 (26–53), 21 (19–25), and 21 (17–28) years; and the duration of illness (DOI was 6 (4–10), 14 (9–20), 4 (2–10), 11 (7–17), and 17 (10–22) years, respectively. Between 1998 and 2019, the percentage of patients undergoing DBS among surgically treated MD patients increased from 0% to 85%, and the shift towards DBS in PD was larger than that shift for dystonia or ET. Conclusion: PD is the most common MD that necessitates surgical treatment, followed by ET and dystonia. Surgical timing is individualized and varies among different types of MDs. DBS has become the dominant surgical modality for MDs.